Synthesis, Spectral Investigation, Reinforced Bio-potential Enhancement and Structure Property Correlation of Mixed Ligand Pyridine-4-carbaldehyde Metal Complexes - Surendra Dilip1, C.; Senguttuvan2, G.; Sivakumar2, V.; Manik, K.; Thiruneelak, R. (Asian Journal of Chemistry, 2013)
Mixed ligand M(II/III) complexes of pyridine-4-carbaldehyde as primary ligand and chloride as secondary ligand have been microwave synthesized and characterized by various physical, analytical and spectral studies viz., FTIR, UV-visible, TG-DTA-DTG and XRD. The molar conductance, magnetic moment values and the electronic spectral data gives a general formula as [M(PA)4Cl2] where M = Mn(II), Co(II), Ni(II), Cu(II) and Cd(II) and [M(PA)3Cl3] where M = Cr(III) and Fe(III) with a distorted octahedral structure. Thermal analyses show that the complexes initially lose molecules of hydration and subsequently expel anionic and organic ligands in continuous steps.